1998
DOI: 10.1038/sj.pcan.4500253
|View full text |Cite|
|
Sign up to set email alerts
|

Three-year prospective study of 3228 clinical BPH patients treated with alfuzosin in General Practice

Abstract: Objectives: To investigate (a) the magnitude and durability of symptom score reduction and HRQL score improvement (including sexual drive); (b) adverse outcomes; and (c) progression to acute urinary retention and prostate surgery up to three years of treatment with alfuzosin.Methods: Three thousand two hundred and twenty-eight BPH-patients out of 812 centers were included in a prospective three-year open-labelled study and treated with alfuzosin (immediate release formulation) at the recommended dosage. A symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 22 publications
(33 reference statements)
0
12
1
Order By: Relevance
“…30 This bene®t has been con®rmed in the three-year open study in 3228 patients in general practice, in which the incidence of AUR was only 0.3%. 31 Although there was no placebo arm, the incidence of AUR in this study was lower than the 2 ± 3% incidence reported in the literature for watchful waiting. 32 Alfuzosin has also been shown to favour return to a normal voiding pattern in a trial without catheter (TWOC) conducted in BPH patients with AUR.…”
Section: Bene®ts Of a A 1 -Blockers On Acute Urinary Retentioncontrasting
confidence: 45%
“…30 This bene®t has been con®rmed in the three-year open study in 3228 patients in general practice, in which the incidence of AUR was only 0.3%. 31 Although there was no placebo arm, the incidence of AUR in this study was lower than the 2 ± 3% incidence reported in the literature for watchful waiting. 32 Alfuzosin has also been shown to favour return to a normal voiding pattern in a trial without catheter (TWOC) conducted in BPH patients with AUR.…”
Section: Bene®ts Of a A 1 -Blockers On Acute Urinary Retentioncontrasting
confidence: 45%
“…The long–term efficacy and safety of alfuzosin has been confirmed in large cohort studies with patients treated for up to 3 years [14, 15, 16]. The good safety profile of alfuzosin has been fully confirmed by post–marketing experience [17].…”
Section: Introductionmentioning
confidence: 75%
“…At 1-year follow-up, the mean Danish Prostate Symptom Score sexual function questionnaire scores showed signifi cant improvement in all of these symptoms, suggesting that alfuzosin is effi cacious in improving LUTS and may be effective in improving sexual function in patients with concomitant ED. These improvements in sexual function have been demonstrated in patients in up to 3 years of follow-up [18]. This apparent improvement in SD has not been noted with the other available α-blockers.…”
Section: Medical Therapymentioning
confidence: 66%